96=2(5x+3)+2(4x)

Simple and best practice solution for 96=2(5x+3)+2(4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 96=2(5x+3)+2(4x) equation:


Simplifying
96 = 2(5x + 3) + 2(4x)

Reorder the terms:
96 = 2(3 + 5x) + 2(4x)
96 = (3 * 2 + 5x * 2) + 2(4x)
96 = (6 + 10x) + 2(4x)

Remove parenthesis around (4x)
96 = 6 + 10x + 2 * 4x

Multiply 2 * 4
96 = 6 + 10x + 8x

Combine like terms: 10x + 8x = 18x
96 = 6 + 18x

Solving
96 = 6 + 18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18x' to each side of the equation.
96 + -18x = 6 + 18x + -18x

Combine like terms: 18x + -18x = 0
96 + -18x = 6 + 0
96 + -18x = 6

Add '-96' to each side of the equation.
96 + -96 + -18x = 6 + -96

Combine like terms: 96 + -96 = 0
0 + -18x = 6 + -96
-18x = 6 + -96

Combine like terms: 6 + -96 = -90
-18x = -90

Divide each side by '-18'.
x = 5

Simplifying
x = 5

See similar equations:

| -4x-27=7x+7 | | y-b=nyb | | x^3y^2+5x^2y-14x=0 | | 5(x+4)+(3x-5)= | | 208=2(5z+2)+2(4z+3) | | 68=.2(20x+50)+2 | | y=-1.60x+b | | -9x^2+35x-30=1-x | | 4y-0.9=5y | | 9(x+5)=6x+2 | | (2+y)(3y+7)=0 | | -3(-5x+2)= | | (8x+1)2+5=10 | | 3x^4+33x^3+90x^2=0 | | -5(4x-2)= | | a^(1/3)*a^(4/3) | | 4x-7x-13=-3x+7-13 | | (6x+2)(3x-5)=(9x-4)(2x+4) | | p^2p/p^-5 | | 2/3x-1=-1/3x-5 | | (2x^4+6y)(2x^4-6y)= | | 2(3x+3)=5(x-4) | | -3(x+5)=2-2x | | 12x^2+4x+15=0 | | 3(7r-12)=21r-6 | | 63+30t+3t^2=0 | | 4x+2.9=9.7 | | 7(x+1)=-2(x-4)+x | | 12k-3(2k-3)=45 | | -5y-15=7y+9 | | -5-15=7y+9 | | 2(1.6x)-1.33=-x+4.13 |

Equations solver categories